Predicting grapevine canopy nitrogen status using proximal sensors and near‐infrared reflectance spectroscopy. Issue 2 (11th March 2021) - Walker, Harriet V.; Jones, Joanna E.; Swarts, Nigel D.; Rodemann, Thomas; Kerslake, Fiona; Dambergs, Robert G.
Abstract: Background : The current method employed by industry for tissue analysis to determine grapevine nitrogen (N) status is expensive and time intensive. Aims : This study explored the use of proximal sensors and Fourier transform near infrared spectroscopy (FT‐NIRS) to predict vine ( Vitis vinifera L.) canopy N status over two growing seasons in Southern Tasmania, Australia. Methods : The GreenSeeker, Crop Circle ACS‐430 and SPAD‐502 proximal sensors were used to measure vine canopies (cv. Pinot Noir and Chardonnay) at three sampling dates (January, February, March) in the 2017/18 growing season, and two (December & February) in the 2018/19 growing season. For 12 replicates consisting of 5 vines each, a 30‐leaf sample was taken for FT‐NIRS and elemental analysis on dried, ground leaf samples. In addition, measurements with a portable FT‐NIRS were taken on fresh leaf samples (2018/19). All measurements were correlated with leaf N concentration (%) determined via elemental analysis. Results : The reliability of the proximal sensors to predict vine N content was dependent on the vine variety and sampling time. FT‐NIRS demonstrated a strong ability to predict vine N concentration independent of season, sampling time and variety. The benchtop FT‐NIRS showed the strongest predictability over both seasons ( r 2 = 0.94), yet the portable FT‐NIRS also showed potential ( r 2 = 0.76). Conclusion : Further investigation of portable FT‐NIRS technology is necessary to provide a robust model for non‐destructive vine N determination in the field.